Preferences of disputes resolution mechanisms in Islamic financial services industry in Malaysia - Mohd. Zain, Nor Razinah; Engku Ali, Engku Rabiah Adawiah; Abideen, Adewale Abideen (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
The groundbreaking reforms in the legal and regulatory framework for Islamic financial services industry in Malaysia open a new phase in the modern history of this market. The financial ombudsman scheme (FOS) is applied by the Ombudsman of Financial Services (OFS) and resembles the classical muhtasib model in Islamic law. Earlier on, the i-Arbitration Rules (Revised 2013) was introduced by the Kuala Lumpur Regional Centre for Arbitration (KLRCA). Focusing in making Malaysia as the global dispute resolution hub for Islamic financial services, this research investigates the preferences of dispute resolution mechanisms among Malaysian retail customers in resolving disputes with their Islamic banks. While employing aqualitative legal approach on the availabilityof dispute resolution mechanisms for Islamic financial services in Malaysia, it is found that Shariah Advisory Council of Bank Negara (SAC) has an essential role as an expert body for reference in disputes involving Islamic financial services. Such reference to SAC is significant in ensuring the Shariah-compliance nature in the disputes of Islamic financial services. A collaborative bridge between the SAC and the institutions that offer dispute resolution mechanism must be built and maintained at all time